Cortical Signal-Driven Kinematic Control: Implementing Human-Arm Like Movements in A 6-Dof Robotic Manipulator Via Non-Invasive BCI - abdulrahman satam, ihab; Szabolcsi, Robert (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The integration of Brain-Computer Interface (BCI) technology with robots has revolutionized assistive solutions for those with motor impairments. Executing basic actions like gripping things or starting a handshake continues to pose a considerable problem for those with neuromuscular limitations. In response to this difficulty, we introduce a new system that utilizes brain signals to operate robotic actuators with exceptional efficiency. This study uses a non-invasive brain-computer interface device known as Emotive Insight, to record neural activity and convert cognitive inputs into immediate robotic control. The suggested system creates a seamless neuro-mechanical communication framework by analysing EEG data using Emotive software and integrating them with an Arduino-based controller. The integration is enabled by the HITI Brain software, providing seamless interaction between cognitive intents and robotic execution. Experimental validation, however performed on a single participant ( the main author) due to Doctoral Study graduation, has shown the system's efficacy in manipulating a six-degree-of-freedom robotic arm. These results highlight its potential use not just in prosthetic limb control but also in wider areas, including mobility aids like wheelchairs, bicycles, and autonomous robotic systems. This work signifies a crucial advancement in connecting human cognition with machine operation, facilitating the emergence of neuro-controlled assistive technology.